Approach via the XI rib of the right subphrenic space - Marella, Muzio S; Mauro, Liber (Cirugía del Uruguay, 2021)
It is planned indications about approaches to subfrenic lodge by way of XI rib in high posterior hydatic liver cysts or hepatic abces. Is important a previous and precise localisation of cyst and its posterior contact. An andtomical functional study of the thoraco abdominal region is made. distinguishing three sectors: interior ( of vertebra!dynamic), intermediate ( of respiratory dynamic) and externa} ( of abdominal girth). .From surgical point of view are distinguished in the XI rib, three sectors: internal ( yuxta-vertebral or of neumotoax region), intermediate ( in relation with mute pleura or surgical) and externa} ( nodal centre of muscles inse'tions). It is pointed out the operative position of the patient and the choice of anesthesic according with the general state of him and the degree of the complication. Are analized the five times of surgical approach, plane by plane that take to the extraperitoneal liver zone through the chirurgical sector of the XI rib. Are given basic details about the drainages and the post operative of hepatic hydatidic surgery.